Image Processing and Analysis for Preclinical and Clinical Applications - Stefano, Alessandro; Comelli, Albert; Vernuccio, Federica (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Radiomics is one of the most successful branches of research in the field of image processing and analysis, as it provides valuable quantitative information for the personalized medicine. It has the potential to discover features of the disease that cannot be appreciated with the naked eye in both preclinical and clinical studies. In general, all quantitative approaches based on biomedical images, such as positron emission tomography (PET), computed tomography (CT) and magnetic resonance imaging (MRI), have a positive clinical impact in the detection of biological processes and diseases as well as in predicting response to treatment. This Special Issue, "Image Processing and Analysis for Preclinical and Clinical Applications", addresses some gaps in this field to improve the quality of research in the clinical and preclinical environment. It consists of fourteen peer-reviewed papers covering a range of topics and applications related to biomedical image processing and analysis.